Remarkable hexafunctional anion receptor with operational urea-based inner cleft and thiourea-based outer cleft: Novel design with high-efficiency for sulfate binding - Maryam Emami Khansari (Nature Portfolio, 2017)
Abstract The recognition of anions by designed receptors has attracted much attention in recent days. In particular, the selective binding of sulfate with artificial receptors is important because of its relevance to many biological and environmental applications. However, the development of organized molecular receptors with high-efficiency for sulfate binding still remains a significant challenge. We report a novel para-phenylene-bridged hexafunctional tripodal receptor that contains a urea-based inner cleft and a thiourea-based outer cleft, providing perfect sites for step-wise binding of two anions within a single cavity. The new receptor was synthesized in a three-step process, and was investigated for its anion binding properties by 1H NMR titrations, 2D NOESY experiments and computational studies. As indicated by solution binding studies, the receptor selectively binds sulfate over other oxoanions, forming a 1:2 stoichiometric complex that is stabilized via strong H-bonding interactions. High-level DFT calculations reveal that the receptor, owing to the enhanced H-bonding ability of thiourea groups, initially encapsulates one sulfate in its thiourea-based outer cleft, followed by a second encapsulation in its urea-based inner cleft. Such a functionalized receptor with the unique combination of urea-based cleft and thiourea-based cleft in a single receptor has not been reported previously.